A note on recordings of Southern right whales (Eubalaena australis) off the coast of Uruguay - Tellechea, Javier S.; Norbis, Walter (J. Cetacean Res. Manage., 2023)
Passive acoustic detection has the potential to provide data regarding the location of right whales. Right whales are not known to produce songs; nonetheless, the call repertoire of Eubalaena australis, the southern right whale, has been exhaustively and quantitatively analysed. This paper describes sound production by southern right whales in the coast of Uruguay (35°S) in the South Atlantic Ocean. No previous study of southern right whale sounds in Uruguayan waters exists. The calls recorded were: Up call, a low tonal call with a frequency of 50Hz to 200Hz; High call, which has the most energy in a range of 200–500Hz, and Pulsive call, a complex mixture made up of amplitude modulated noise and tones, 50– 200Hz. This is the first acoustic study of E. australis in this region and focusses on the occurrence of calls previously identified by Clark to obtain more information about the acoustic behaviour of this cetacean in Uruguayan coastal waters. Future efforts will be made to obtain more recordings in different locations along the coast of Uruguay, where annual sightings occur. Such information is essential for examining global differences between vocalisations of southern right whales.